Simulating PIP2-Induced Gating Transitions in Kir6.2 Channels - Bründl, Michael; Pellikan, Sarala; Stary-Weinzinger, Anna (Frontiers in Molecular Biosciences, 2021)
ATP-sensitive potassium (KATP) channels consist of an inwardly rectifying K+ channel (Kir6.2) pore, to which four ATP-sensitive sulfonylurea receptor (SUR) domains are attached, thereby coupling K+ permeation directly to the metabolic state of the cell. Dysfunction is linked to neonatal diabetes and other diseases. K+ flux through these channels is controlled by conformational changes in the helix bundle region, which acts as a physical barrier for K+ flux. In addition, the G-loop, located in the cytoplasmic domain, and the selectivity filter might contribute to gating, as suggested by different disease-causing mutations. Gating of Kir channels is regulated by different ligands, like Gβγ, H+, Na+, adenosine nucleotides and the signaling lipid phosphatidyl-inositol 4,5-bisphosphate (PIP2), which is an essential activator for all eukaryotic Kir family members. Although molecular determinants of PIP2 activation of KATP channels have been investigated in functional studies, structural information of the binding site is still lacking as PIP2 could not be resolved in Kir6.2 cryo-EM structures. In this study, we used Molecular Dynamics (MD) simulations to examine the dynamics of residues associated with gating in Kir6.2. By combining this structural information with functional data, we investigated the mechanism underlying Kir6.2 channel regulation by PIP2.